Modeling no-jam traffic in ant trails: a pheromone-controlled approach. (22nd May 2018) - Guo, Ning; Hu, Mao-Bin; Jiang, Rui; Ding, Jianxun; Ling, Xiang
Abstract: The experiment in John et al (2009 Phys. Rev. Lett .102 108001) shows that when ants move in a single-file trail, no jam emerges even at very high densities. We propose a self-propelled model of ant traffic to reproduce the fundamental diagram without a jammed branch. In this model, ants can adjust their desired velocities actively by perceiving pheromone concentration near the front of the trail. Moreover, ants will bear the repulsive force when they have physical contact with neighbors. The velocity in the simulation decreases slightly with increasing density, which captures the main feature observed in the experiment. Distributions of velocity and distance headway basically also conform to the experimental ones.